2020
DOI: 10.1371/journal.pone.0230189
|View full text |Cite
|
Sign up to set email alerts
|

Association of atrial fibrillation and clinical outcomes in adults with chronic kidney disease: A propensity score-matched analysis

Abstract: Objective Atrial fibrillation (AF) is associated with adverse outcomes in the general population, but its impact on patients with chronic kidney disease (CKD) remains unclear. In this study, we assessed the association between AF and risks of all-cause mortality and stroke in Chinese adults with CKD. Methods We enrolled adults aged 45 years or older with CKD (defined as an estimated glomerular filtration rate <60 mL/min per 1.73 m 2 and/or proteinuria identified using the urine dipstick method) from the Kailua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Several previous studies investigated the association between stroke and atrial fibrillation in patients with chronic kidney disease [ 2 , 23 25 ]. In a Swedish study, it was shown that patients with atrial fibrillation had a two-fold increased risk of ischemic stroke in patient with an eGFR below the 60 ml/min /1.73 m 2 [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies investigated the association between stroke and atrial fibrillation in patients with chronic kidney disease [ 2 , 23 25 ]. In a Swedish study, it was shown that patients with atrial fibrillation had a two-fold increased risk of ischemic stroke in patient with an eGFR below the 60 ml/min /1.73 m 2 [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish study, it was shown that patients with atrial fibrillation had a two-fold increased risk of ischemic stroke in patient with an eGFR below the 60 ml/min /1.73 m 2 [ 2 ]. In a study from China, atrial fibrillation was associated with a two-fold increased risk of ischemic stroke in patients with chronic kidney disease [ 23 ]. Another study, that used diagnostic codes for atrial fibrillation and stroke event and did not take albuminuria into account, showed increased ischemic stroke rates with decreasing eGFR [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a clinical perspective, there are many crucial aspects to consider when treating patients with AF and renal impairment. Most importantly, patients with AF suffer from an increased risk of all‐cause death and stroke, and these risks are amplified in those with co‐existing renal impairment 5 . Preventive strategies include the use of anticoagulation therapy such as warfarin, which has been shown to be influenced by renal impairment and consequently linked to poor outcomes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, patients with AF suffer from an increased risk of all‐cause death and stroke, and these risks are amplified in those with co‐existing renal impairment. 5 Preventive strategies include the use of anticoagulation therapy such as warfarin, which has been shown to be influenced by renal impairment and consequently linked to poor outcomes. 6 Alternatively, non‐vitamin K antagonist oral anticoagulants (NOACs) may be used but these agents have varying degrees of renal excretion.…”
Section: Introductionmentioning
confidence: 99%